Recovery of an injured corticospinal tract via an unusual pathway in a stroke patient: Case report. Issue 7 (February 2019) - Jang, Sung Ho; Chang, Chul Hoon; Jung, Young Jin; Seo, You Sung
Abstract: Rationale: A few mechanisms of recovery from an injured corticospinal tract (CST) in stroke patients have been reported: recovery of an injured CST through (1) normal CST pathway, (2) peri-lesional reorganization, and (3) shifting of the cortical origin area of an injured CST from the other areas to the primary motor cortex. However, it has not been clearly elucidated so far. Patient concerns: A 57-year-old male patient presented with complete weakness of the right extremities due to an intracerebral hemorrhage (ICH) in the left basal ganglia. At three weeks after onset, the patient showed severe weakness of his right upper and lower extremities (Motricity Index [MI]: 28/100, finger extensor: 0/5). At 6 months after onset, his weakness showed some recovery, however, right finger extensor did not show any recovery (MI: 51/100, finger extensor: 0/5). At 9 months after onset, weakness showed significant recovery, particularly right finger extensor (MI: 64/100, right finger extensor: 3/5) and similar motor function persisted until 11 months after onset (MI: 67/100, right finger extensor: 3/5). Diagnoses: The patient was diagnosed as the right hemiplegia due to ICH in the left corona radiata and basal ganglia. Interventions: Clinical assessment, transcranial magnetic stimulation (TMS), and diffusion tensor tractography (DTT) were performed at 1, 6, 9, and 11 months after onset. Outcomes: Discontinuation of the left CST at the midbrain level was observed on 1-month DTT and the corona radiata on 6-month DTT. However, on 9-month DTT, we observed a CST branch originating from the left posterior parietal cortex and then connecting to the main truck to the CST at the thalamic level and thickened on 11-month DTT. On 1-month TMS, no MEP was evoked from the left hemisphere; on 6-month TMS study, MEPs were obtained at a right hand muscle (latency: 22.8 ms, amplitude: 130 μV) and its amplitude was increased as 300 μV with similar latencies on 9- and 11-month TMS studies. Lessons: Recovery of an injured CST via an unusual pathway was demonstrated in a hemiparetic patient with ICH, using DTT and TMS. We believe that our results suggest that precise evaluation for an injured CST using TMS and DTT might be necessary, particularly in young patients, even after 6 months from onset even though the stroke patients show clinical characteristics of severe injury of the affected CST.